Intensity-Duration-Frequency Relationships of intense rainfall in Lages, SC - Werner, Romeu Souza; Bertol, Ildegardis; Barbosa, Fabrício Tondello (Revista de Ciências Agroveterinárias, 2024)
Knowledge of rainfall intensity is essential for planning hydraulic works. With the aim of filling the lack of this information for conservation planning in rural areas, this work aimed to determine the empirical constants of the heavy rainfall equations using precipitation data, and the adjustments of these equations to the observed precipitation. The rainfall data were obtained in equipment (pluviograph and pluviometer) located to the meteorological at the station of the Center for Agro-Veterinary Sciences, in Lages city, Santa Catarina state, Brazil, from 1989 to 2016 (28 years). To obtain the height and intensity of the rainfall in the return periods of 2, 5, 10, 15, 20, 25, 30, 40 and 50 years, the statistical distribution of Gumbel was applied. Parameters were obtained for rainfall periods of up to 240 minutes (Equation I) and from 360 to 1,440 minutes (Equation II). The frequency of intense rain estimated by the Gumbel method, with adherence tested using the Anderson-Darling test, adjusts to the frequency of rain observed in the Lages city. This provides reliability of the probabilistic distribution of the observed data for certain return times and duration of rainfall. The intensity-duration-frequency (IDF) equation fits rainfall data observed over a 28-year and can be used to predict the maximum average rainfall intensity. The IDF I equation is i=1,285.65Tr0.133(t+14.2)-0.87, applied to rainfall lasting up to 240 minutes, and the IDF II equation is i=1,923.06Tr0.188(t +34.85)-0.86, applied to rainfall lasting between 360 and 1,440 minutes.